Feasibility of double-skin façades for multi-storeys office buildings in Amman/Jordan: an insight into thermal performance for both summer and winter peak conditions - Amaireh, Ikrima; Gan, Guohui; Omer, Siddig; Zeinelabdein, Rami (2017)
Amman, the capital city of Jordan, usually experiences a hot dry summer with high solar radiations and a cold-wet winter. While the entire state of Jordan faces serious shortages in energy sources, significant growth in both industrial investment and constructions is noticed in the last few years particularly in Amman. This includes construction of both apartment and office buildings using a relatively new construction systems/elements. In Amman, for instance, Double-skin facades (DSF) have recently been introduced to a few buildings. However, there are no noticeable studies showing how it will work under the climate of Amman. Literature from similar climates indicates that while DSF is expected to perform well in winter, summer overheating is a major problem in hot regions due to large glazed surfaces facing excessive direct solar gains that coincide with high ambient temperatures. Thus, it is highly important to investigate the operational performance of this relatively new system in such a climate before it is widely applied due to its advantages as a promising passive technology. This study aims to investigate the thermal performance of DSF integrated into office buildings in Amman. Intended work was conducted using TAS tool and based on Amman’s weather file. Results showed that integration of DSF into multi-storeys office buildings would generally increase indoor operative temperatures for both conditions. While this would lead to significant overheating in summer times, indoor thermal comfort would almost be achieved in winter with a slight possibility of overheating during peak hours. However, the reasonable operation of the system (i.e. openings control) would help to overcome potential overheating in winter, whereas applying passive cooling technologies is highly recommended for summer operation.